Working in the context of austerity : challenges and struggles / edited by Donna Baines and Ian Cunnningham. - Baines, Donna, 1960-; Cunningham, Ian (Bristol University Press, 2021)
Austerity was presented as the antidote to sluggish economies, but it has had far-reaching effects on jobs and employment conditions. With an international team of editors and authors from Europe, North America and Australia, this illuminating collection goes beyond a sole focus on public sector work and uniquely covers the impact of austerity on work across the private, public and voluntary spheres. Drawing on a range of perspectives, the book engages with the major debates surrounding austerity and neoliberalism, providing grounded analysis of the everyday experience of work and employment.